Analisis Dampak Pemilihan Lokasi Terhadap Keberlanjutan Dan Efisisensi Pelabuhan Perikanan Berdasarkan Literatur Yang Ada - Hutabarat, Krismail Devkenan; Hulu, Hertin Kartika Putri; Telaumbanua, Betzy Victor (CV. SINAR HOWUHOWU, 2025)
Fishing ports play a crucial role in supporting the sustainability and efficiency of the fisheries system, starting from the process of landing catches to distribution and marketing. This study aims to analyze the impact of fishing port location selection on operational efficiency and sustainability of fisheries resources in Indonesia, using a literature study approach. The results of the study show that proper site selection can reduce logistics costs, improve market access, and encourage coastal economic growth. Conversely, inappropriate locations have the potential to create operational bottlenecks, environmental pollution, and social conflicts. Factors such as water depth, accessibility, environmental conditions, and the involvement of local communities need to be considered comprehensively. An ecosystem-based and participatory approach is key in ensuring that the port built is able to support environmental sustainability and community welfare. Therefore, planning the location of fishing ports should involve multidisciplinary studies that integrate technical, social, environmental, and regulatory aspects to produce effective, inclusive, and sustainable development decisions.